Employer Responses to Workers' Compensation Insurance Experience Rating - Kralj, Boris (Relations industrielles / Industrial Relations, 1994)
This paper investigates the impact of an Insurance premium experience rating mechanism that is designed to induce firms to reduce the incidence of workplace accidents and accident daims costs. Logit model analysis of survey-response data and case study information are used to analyze the impact of the introduction of workers compensation Insurance premium experience rating on employer behaviour in Ontario. The key result is that the financial incentives provided by experience rating have induced employers to alter their behaviours and undertake strategies aimed at both accident prevention (reducing accident frequency rates) and reducing workers ' compensation claims costs.